Scenarios of power : myth and ceremony in Russian monarchy from Peter the Great to the abdication of Nicholas II - Wortman, Richard (Studies of the Harriman Institute., 2006)
This new and abridged edition of Scenarios of Power is a concise version of Richard Wortman's award-winning study of Russian monarchy from the seventeenth century until 1917. The author breaks new ground by showing how imperial ceremony and imagery were not simply displays of the majesty of the sovereign and his entourage, but also instruments central to the exercise of absolute power in a multinational empire. In developing this interpretation, Wortman presents vivid descriptions of coronations, funerals, parades, trips through the realm, and historical celebrations and reveals how.